Luminescent methacrylic copolymers with side-chain cyclometalated iridium(III) complexes. (January 2019) - Baschieri, Andrea; Monti, Filippo; Armaroli, Nicola; Mazzotti, Giovanni; Giorgini, Loris; Sambri, Letizia; Benelli, Tiziana
Abstract: A series of eight copolymers made of a poly (methyl methacrylate) backbone with a luminescent iridium(III)-based pendant is presented. These materials are obtained by radical copolymerization of different ratios of methyl methacrylate (MMA) with the reactive Ir-based MMA monomer [Ir(ppy) 2 (ptmma)]Cl (Hppy = 2-phenylpyridine, ptmma = 11-(4-pyridin-2-yltriazol-1-yl)undecyl 2-methylprop-2-enoate). The products are characterized by NMR, IR and DSC methods. The specific ratio among the two monomers, dictates the concentration of the emissive iridium-based centers along the polymer backbone, which affects the overall luminescence behavior of the material. The position of the absorption and emission maxima of the iridium-based monomer and of the related polymeric compounds are virtually identical, pinpointing the optically innocent character of the polymer matrix. Photophysical investigations show that the emission quantum yields (PLQYs) of the iridium-based emitters improve upon increasing the fraction of the inert MMA co-monomer, due to a progressive decrease in self-absorption and self-quenching, approaching the infinite-dilution limit at the relatively low [MMA]:[Ir] molar ratio of 500, with PLQY = 0.51 ± 0.05. The concentration-quenching rate process follows a power-law proportional to R –(2.6±0.9), where R is the calculated average distance between the emitting units of the copolymers. Such a deviation from the expected dipole-dipole interaction ( i.e., R −6 dependence) suggests the partial formation of aggregates leading to the occurrence of static self-quenching in the solid matrix, as the concentration of the iridium centers increases. These results offer valuable hints for the formulation of strongly emitting hybrid materials in which a high concentration of triplet luminophores is embedded in organic polymers solely serving as solid transparent scaffolds. Graphical abstract: Image 1 Highlights: Synthesis of new methacrylic copolymers bearing luminescent Ir(III)-based pendants. Preparation of strongly luminescent materials with high load of Ir centers. Useful results for the optimization of luminescent solar concentrators (LSCs).